The implementation of authentic assessment in history learning at senior high school - Sulis Setiani Kusuma Dewi; Aman Aman (Journal of Social Studies (JSS), 2020)
This study aims to describe the implementation of authentic assessment in history learning in Senior High School (SMA), which is adjusted with assessment procedures related to the judgment of competencies that have been made by the government. This study is a qualitative naturalistic study conducted in SMA N 1 Ngaglik and SMA N 2 Sleman, Yogyakarta. The technique of data collection was done through observation, interview, and documentation. The data analysis technique was done by triangulation. The result of the study shows that: both schools carried out an authentic assessment in learning activities, although in its application, there some shortcomings. 1) Planning, both schools have been made a planning assessment that includes attitude assessment, knowledge, and skill assessment, although the teacher of history in both schools still has not made a grid for knowledge assessment. 2) Appraisal, both schools conducted attitude assessment through observation technique and peer assessment, while SMA N 2 Sleman conducted attitude assessment by self-assessment technique. Knowledge assessment was conducted by the workbook, Deuteronomy, PTS, and PAS; besides written tests assessment in SMA N 2, Sleman was also undertaken by oral tests. They were assessing skill both of school conducted by using performance assessment in papers form. 3) Processing of attitude assessment activity conducted by doing coordinating with BK teachers and homeroom teachers. While assessing knowledge and skill performed by calculating average the value obtained. 4) Follow-up activities carried out by conducting written tests, whereas, in SMA N 1, Ngaglik added an oral test technique.